2006
DOI: 10.1159/000095338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen and Related Agents upon Methamphetamine-Induced Neurotoxicity within an Impaired Nigrostriatal Dopaminergic System of Ovariectomized Mice

Abstract: Estrogen increases methamphetamine (MA)-induced neurotoxicity within the impaired nigrostriatal dopaminergic (NSDA) system of ovariectomized female mice, as defined by enhanced striatal dopamine (DA) depletion. In this study we compared the effects of a lower dose of estradiol benzoate (EB, 1 µg) with related agents – tamoxifen (TMX, 12.5 µg), testosterone (5 µg) and dehydroepiandrosterone (DHEA, 3 mg) in this paradigm. In experiment 1, ovariectomized mice received an initial treatment with MA. At 1 week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Other reports have shown that estrogens increase dopamine synthesis in the SN (presynaptic effects), and also increases release of dopamine from nigral axon terminates within the striatum (postsynaptic effects). In rodents and in neuronal cell culture studies, estrogens have been shown to protect dopaminergic neurons from injury (Liu and Dluzen, 2006;Arvin et al, 2000).…”
Section: Groupmentioning
confidence: 99%
“…Other reports have shown that estrogens increase dopamine synthesis in the SN (presynaptic effects), and also increases release of dopamine from nigral axon terminates within the striatum (postsynaptic effects). In rodents and in neuronal cell culture studies, estrogens have been shown to protect dopaminergic neurons from injury (Liu and Dluzen, 2006;Arvin et al, 2000).…”
Section: Groupmentioning
confidence: 99%
“…In ovarectomized mice, studies show that estrogen partly blocks metamphetamine-induced striatal dopaminergic depletion. [37][38][39] Tamoxifen, a selective estrogen receptor modulator, presents a neuroprotective effect against methamphetamine and methoxy-phenyltetrahydropyridine-induced toxicity when used alone but abolishes estrogen's positive effects when combined with this hormone. 40 We have observed PD patients whose initial symptom of metastatic carcinoma was marked exacerbation of parkinsonian symptoms, which became non-levodopa responsive (J. Jankovic, personal observation).…”
Section: Does Pd Increase Risk Of Cancer?mentioning
confidence: 99%
“…Tamoxifen, a selective estrogen receptor modulator with mixed agonist/antagonist action, is used in the prevention and treatment of breast cancer (4). Animal studies have shown a neuroprotective role of estrogen and tamoxifen at the nigrostriatal dopamine pathway; however, this finding has not been ubiquitous (5,6). Increased dopamine release (directly or indirectly through modulating dopamine receptor function) and modulation of membrane dopamine transporter activity have been postulated as some of the neuroprotective mechanisms of estrogen (5,6).…”
Section: Aripiprazole-induced Tardive Dyskinesia: the Role Of Tamoxifenmentioning
confidence: 99%